Minimal hepatic encephalopathy identifies patients at risk of faster cirrhosis progression. Issue 3 (22nd February 2018) - Ampuero, Javier; Montoliú, Carmina; Simón‐Talero, Macarena; Aguilera, Virginia; Millán, Raquel; Márquez, Celina; Jover, Rodrigo; Rico, María Carmen; Sendra, Carmen; Serra, Miguel Ángel; Romero‐Gómez, Manuel
Abstract: Background and Aim: Minimal hepatic encephalopathy (MHE) predicts poor prognosis and could reflect an advanced liver disease. We aimed to assess whether MHE could be a surrogate marker of a further liver disease. Methods: Prospective multicenter study including 320 cirrhotic patients, followed for up to 5 years, which were classified at baseline in compensated cirrhosis without (stage 1) and with varices (stage 2), one decompensating event (stage 3), and any second decompensating event (stage 4). Cirrhosis progression was defined by a transition towards a different stage (competing events: liver transplant due to hepatocellular carcinoma and non‐liver‐related death). MHE was detected by critical flicker frequency and psychometric tests. Results: Minimal hepatic encephalopathy was diagnosed in 18.2% (57/314) of patients. Cirrhosis progression occurred in 38.1% (122/320) of patients, while liver transplant was required in 10.9% (35/320), and 19.1% (61/320) died. In competing risk regression, MHE was associated with disease progression: model 1 subhazard ratio [sHR] 2.34 [95%confidence interval (CI) 1.58–3.46]; P = 0.0001; model 2 [sHR 2.18 (95%CI 1.43–3.33); P = 0.0001]; model 3 [sHR 2.48 (95%CI 1.63–3.76); P = 0.0001]. The annual incidence rate of progression was higher in MHE patients: stage 1 (19.4 vs 5.6 cases per 100 person‐years); stage 2 (26.8 vs 15.6); stage 3 (45.7 vs 16.5); and stage 4 (40.7 vs 12.8). MHE showed a higher cumulative incidence of disease progression from the first year in decompensated and the third year in compensated cirrhosis. Conclusion: Minimal hepatic encephalopathy was associated with cirrhosis progression and showed a higher cumulative and annual incidence rate of disease progression. MHE could be a surrogate marker of disease progression, irrespective of cirrhosis status, identifying patients at risk of suffering a more aggressive cirrhosis form.